The Health Effects of Dietary Nitrate on Sarcopenia Development: Prospective Evidence from the UK Biobank - Jigen Na; Yuefeng Tan; Yanan Zhang; Xiaona Na; Xiaojin Shi; Celi Yang; Zhihui Li; John S. Ji; Ai Zhao (Foods)
Nitrate is abundant in natural foods, especially plant-based foods, having the potential to enhance muscle function. However, its relationship with sarcopenia in the context of daily diet remains unexplored. This cohort study investigated the associations between dietary nitrate intake and sarcopenia, as well as related symptoms, using data including 28,229 participants with a mean follow-up of 9.37 years from the UK Biobank. Dietary nitrate intake was estimated using a comprehensive nitrate food database. Adjusted logistic regression models suggested potential inverse associations between total nitrate intake and risks of sarcopenia plus pre-sarcopenia (Sarc-Presarc), low hand grip strength (HGS), and low walking pace. Similar results were primarily observed for nitrate from plant-based foods. With higher intake, females appeared to have higher HGS and a decreased risk of Sarc-Presarc, while males exhibited a reduced risk of low walking pace. The inverse association between nitrate intake and low skeletal muscle mass index was more evident in individuals aged 65 and above. These associations seemed independent of antioxidants, though higher antioxidants might augment the protective effect against low walking pace. Mediation analyses indicated that protein homeostasis and blood pressure might mediate these associations. These findings suggested that a higher dietary nitrate intake from plant-based foods could contribute to sarcopenia prevention, though further research is needed to confirm these observations.